Arabic-KAFA: an augmented reality application for learning Arabic vocabulary - Mohamad Yusof, Mohd Akashah; Ismail, Nasirah; Zakaria, Muhamad Zaidi; Wan Daud, Wan Ab Aziz; Abdul Ghani, Muhammad Taufiq (Universiti Teknologi MARA, Kedah, 2023)
This study aims at explaining the design and development process for ARabic-KAFA application for learning KAFA Arabic vocabularies. Students at primary level especially at KAFA institutions are in need to a multimedia platform due to scarcity of multimedia learning materials as an additional method to the current traditional method of learning Arabic vocabulary. Therefore, ARabic-KAFA is designed and developed based on design and development approach (DDR) and Scaffolding theory to shed light on heautagogy approach through multimedia augmented reality platform for KAFA students to learn KAFA Arabic in a better environment.